Legal Problems in the Use of Banking Credit Cards in Indonesia - Susanty, Ade Pratiwi (International Journal of Law and Public Policy (IJLAPP), 2020)
One of the banking products in the credit sector that is becoming a trend in Indonesia is a credit card. Almost everyone who has worked has a credit card. Credit cards are usually used to facilitate payment transactions when shopping. This research aims to explain about credit cards, credit card regulations in Indonesian laws and regulations, and legal problems in the use of banking credit cards. The method used in this research is normative legal research, using a statutory approach. The research results explain that a credit card is a card-based payment instrument that can be used to make payments for obligations arising from an economic activity, including spending transactions and / or to make cash withdrawals, where the cardholder's payment obligations are first fulfilled by the acquirer or issuer, and the cardholder is obliged to make payments at the agreed time, either in lump sum (charge card) or by payment in installments. Legal problems that often occur between banks and customers using Credit Cards are defaults committed by customers because they don’t pay Credit Card bills or fines billed to them and the use of debt collector services by the bank in invoicing credit card users.